Exploring the Potency of Nigella sativa Seed in Inhibiting SARS-CoV-2 Main Protease Using Molecular Docking and Molecular Dynamics Simulations - Ari Hardianto; Muhammad Yusuf; Ika Wiani Hidayat; Safri Ishmayana; Ukun Mochammad Syukur Soedjanaatmadja (Indonesian Journal of Chemistry, 2021)
Coronavirus disease (COVID-19) is a pandemic burdening the global economy. It is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Black cumin (Nigella sativa) seed may contain antivirals for the disease since it was reported to inhibit the human immunodeficiency virus (HIV) and hepatitis C virus (HCV). Main protease (Mpro) is a vital protein for viral replication and a promising target for COVID-19 drug development. Hence, in this study, we intended to uncover the potency of N. sativa seed as the natural source of inhibitors for SARS-CoV-2 Mpro. We collected secondary metabolites in N. sativa seed through a literature search and employed Lipinski’s rule of five as the initial filter. Subsequently, virtual screening campaigns using a molecular docking method were performed, with N3 inhibitor and leupeptin as reference ligands. The top hits were analyzed further using a molecular dynamics simulation approach. Molecular dynamics simulations showed that binding affinities of nigellamine A2 and A3 to Mpro are comparable to that of leupeptin, with median values of -43.9 and -36.2 kcal mol–1, respectively. Ultimately, this study provides scientific information regarding N. sativa seeds’ potency against COVID-19 and helps direct further wet experiments.